Amnion membrane for coverage of gingival recession: A novel application - Rucha Shah; N K Sowmya; D S Mehta (Wolters Kluwer Medknow Publications, 2014)
Introduction: Amnion allograft has been used in the field of medicine for its exceptional wound-modulating properties. However, in the field of dentistry, only a limited number of reports have explored its potential in healing of oral wounds. Materials and Methods: Amnion allograft in conjunction with coronally advanced flap has been used in the management of gingival recession. Results: A complete coverage along with excellent esthetics and an improvement in gingival biotype was observed at 6 months postoperatively. Discussion: Because of its inherent wound-modulating properties, amnion allograft may be used to enhance periodontal wound healing and enable tissue regeneration such as that in the coverage of gingival recession. Conclusion: Amnion allograft may provide an alternative to other conventional methods of treating gingival recession.